Design and Prototyping of an Electronic Cane for an Indoor Guide System for the Blind - Gonzalez Gomez, Arnaldo Andres; Díaz Gutiérrez, Yesid; Flórez Barboza, Wilson David (Ingeniería, 2020)
Context: Blindness is a physical-sensory disability that limits the ability of affected people to carry out daily-life activities and deteriorates their quality of life. It is estimated that there are 296.000 blind people throughout the Colombian territory. Method: This article presents the development of an electronic baton that works with a system of guiding lines and information points, together with an application for mobile devices. This research is based on the quantitative method, seeking to investigate the characteristics of the device in terms of its use. A descriptive investigation is performed which can be classified as ex post facto. Results: As a result, a device is developed which can guide a blind person to their destination in closed areas, although the time used for movement is greater compared to a journey with human assistance. Conclusions: There are solutions aimed at guiding a blind person in closed spaces that achieve this goal, although they require bulky hardware, which prevents the dimensions of the device from resembling those of the walking sticks normally used as a tool by the blind population. This limits the natural use of this kind of devices.